2019
DOI: 10.15320/iconarp.2019.95
|View full text |Cite
|
Sign up to set email alerts
|

Re-coding The Characteristics of Public Spaces: The Case of İstanbul

Abstract: This study proposes a quantitative assessment method to ascertain urban square potential at 12 gates of the historic city wall where different typologies, characteristics and periodic features are observed in Fatih district of Istanbul. The quantitative assessment method is based upon a series of indexes including 7 factors in total consisting of 35 indicators. The proposed method developed an "urban square potential index", making use of "transport and accessibility", "convex size", "builtup environment", "pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Sub-regions of the squares Zahrah, 2012;Yeganeh & Kamalizadeh, 2018;Zakariya et al, 2014). Some studies comparatively measure the quality of squares and public open spaces with the indexes created by mathematical expression of the variables obtained using survey and observation techniques (Mehta, 2014;Terzi et al, 2019;Praliya & Garg, 2019). The study on market squares, which is a public space that reflects intense human interaction, has revealed that there is a connection between the built environment, human relations and well-being (Agboola et al, 2018).…”
Section: Literature Review On Spatial Configuration and Spatial Quality Of Public Spacesmentioning
confidence: 99%
See 1 more Smart Citation
“…Sub-regions of the squares Zahrah, 2012;Yeganeh & Kamalizadeh, 2018;Zakariya et al, 2014). Some studies comparatively measure the quality of squares and public open spaces with the indexes created by mathematical expression of the variables obtained using survey and observation techniques (Mehta, 2014;Terzi et al, 2019;Praliya & Garg, 2019). The study on market squares, which is a public space that reflects intense human interaction, has revealed that there is a connection between the built environment, human relations and well-being (Agboola et al, 2018).…”
Section: Literature Review On Spatial Configuration and Spatial Quality Of Public Spacesmentioning
confidence: 99%
“…The squares that reflect the identities and images of the cities contribute to urban life such as creating social memory, increasing activities and socialization. Squares as places that bring people together, increase the quality of life and create a sense of belonging (Walzer, 1986;Mazumdar, 2007) are common spaces where local culture, lifestyle and collective memory are kept alive, social relations are shaped, and daily life activities and rituals are held (Zengel, 2007;Terzi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%